RECENT VOLCANISM OF NORTHERN EURASIA: REGIONALIZATION AND FORMATION SETTINGS - Laverov N.P.; Kovalenko V.I.; Yarmolyuk V.V.; Bogatikov O.A.; Sakhno V.G.; Gurbanov A.G.; Kudryashova E.A.; Akinin V.V.; Evdokimov A.N.; Pevzner M.M.; Ponomareva V.V. (My University, 2006)
In the framework of studies under the “Variations of Environment and Climate: Natural Disasters” program of the Presidium of the Russian Academy of Sciences, we compiled the map of recent volcanism of northern Eurasia on the GIS basis and outlined volcanic regions with different compositions of igneous rocks, evolution of volcanism, and geological conditions of its development. A series of thematic maps (maps of topography, neotectonics, recent faults, and distribution of earthquake sources) represented by separate sheets served as a structural base of the GIS layout.